ANALISIS KEGIATAN SABTU LITERASI TERHADAP KETERAMPILAN MENULIS TEKS NARASI SISWA KELAS V SD MUHAMMADIYAH 3 SURABAYA DI MASA PANDEMI COVID-19 - Muizz, Abdul; Mirnawati, Lilik Binti; Naila, Ishmatun (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
The purpose of this study is to describe how literacy Saturday activities affect the skills of writing narrative texts for fifth grade students at SD Muhammadiyah 3 Surabaya during the pandemic. This research is a qualitative descriptive study with data obtained from several sources, including: The Fifth Grade Teachers, Librarians, and Students of The Fifth Grade. The techniques used in this research are participant observation, unstructured interviews, and documentation. The data analysis technique used is the Miles and Huberman model which consists of data reduction, data presentation, and conclusions. The results of this study, namely Saturday Literacy is a literacy activity carried out on Saturdays, which lasts 45 minutes. Students are asked to read the narrative text in pdf form, then retell it in written form. In addition, this activity is useful in increasing their narrative text writing skills, and this bold literacy Saturday activity is suitable for use during a pandemic.